Costus igneus Spiral Flag, Fiery Costus: FPS151/FP151, 6/2007 - Gilman, Edward (EDIS, 2007)
This document provides a detailed description of the Costus igneus, commonly known as the spiral flag or fiery costus. It highlights the plant’s characteristics, including its large, dark green leaves with light purple undersides, and its striking orange flowers that bloom in the warm months. The plant is a tropical evergreen, suitable for USDA hardiness zones 9B through 11, and is often used as an accent plant in gardens. It thrives in fertile soil with ample moisture and can be propagated by division, cuttings, or separating offsets. The document also notes that mites and nematodes can be problematic, especially in sandy soils, but no major diseases affect the plant. Original publication date October 1999.